Mechanisms of monoclonal antibody stabilization and release from silk biomaterials - Guziewicz, Nicholas A. (2013)
The availability of stabilization and sustained delivery systems for antibody therapeutics remains a major clinical challenge, despite the growing development of antibodies for a wide range of therapeutic applications due to their specificity and efficacy. A mechanistic understanding of protein-matrix interactions is critical for the development of such systems and is currently lacking as a mode to guide the field. We report mechanistic insight to address this need by using well-defined matrices based on silk gels, in combination with a monoclonal antibody. Variables including antibody loading, matrix density, charge interactions, hydrophobicity and water access were assessed to clarify mechanisms involved in the release of antibody from the biomaterial matrix. The results indicate that antibody release is primarily governed by hydrophobic interactions and hydration resistance, which are controlled by silk matrix chemistry, peptide domain distribution and protein density. Secondary ionic repulsions are also critical in antibody stabilization and release. Matrix modification by free methionine incorporation was found to be an effective strategy for mitigating encapsulation induced antibody oxidation. Additionally, these studies highlight a characterization approach to improve the understanding and development of other protein sustained delivery systems, with broad applicability to the rapidly developing monoclonal antibody field.